Analysis of PT. Customer Service Quality. PLN (Persero) UP3 Tanjung Karang In Increasing Customer Loyalty - Ketut Yudi Feryana; M.Oktaviannur (International Journal of Business and Quality Research, 2025)
The quality of customer service plays a crucial role in the success of an organization, especially in the energi supply sector such as PT. PLN (Persero). This research aims to analyze the role of human resource management (HR) in improving the quality of customer service at PT. PLN (Persero) Customer Service Implementation elemen (UP3) Tanjung Karang. The research method used was a pengamatan with a questionnaire distributed to employees and customers of PT. PLN (Persero) UP3 Tanjung Karang. The research results show that HR management has a significant impact on the quality of customer service. Factors such as recruitment, training, and employee development have a positive relationship with customer satisfaction. In addition, intern communication, employee motivation and reward systems also have an important role in improving employee performance and directly contributing to the quality of service provided to customers. This research contributes to the understanding of the close relationship between HR management and customer service quality in the context of the energi industry. The practical implications of this research can help PT. PLN (Persero) UP3 Tanjung Karang in optimizing HR management strategies to increase customer satisfaction and maintain competitiveness in the competitive energi market. The conclusions of this research provide a inti for similar companies to better understand the importance of the role of HR management in achieving strategic goals related to customer service quality.